The EU and neighbors : a geography of Europe in the modern world - Blouet, Brian W., 1936- (John Wiley & Sons, 2012)
"The 2nd edition of Europe increases awareness and understanding of Europe and instills incredible diversity that exists in that region, and for readers to appreciate that diversity.It uses the European Union as an organizing focus while discussing modern events in two sections. The systematic section covers the environment, cultural geography, population, settlement systems, economies, and political geography. The regional section examines Europe on a country-by-country basis"--Resumé vydavatele
Terminologický slovník
Keywords: Evropská unie; regionální geografie -- země Evropské unie; regionální geografie -- Evropa; ekonomická integrace -- Evropa; evropská integrace; regional geography -- European Union countries; regional geography -- Europe; economic integration -- Europe; European integration; Evropa; země Evropské unie; Europe; European Union countries; přehledy; surveys